The Relationship Between Medication Adherence And A Low Salt Diet With The Incidence of Readmission In Heart Failure Patients at RSUD Kota Depok: Hubungan Kepatuhan Minum Obat Dan Diet Rendah Garam Terhadap Kejadian Readmission Pada Pasien Gagal Jantung Di RSUD Kota Depok - Selvina Yuliana; Tarwoto (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Heart failure is a condition where the heart cannot pump enough blood to meet the body's needs. Heart failure is a noncommunicable disease that is the leading cause of death worldwide every year. Readmission is the re-hospitalization ofa patient who has previously returned home to receive inpatient treatment at a hospital. Heart failure patients whoexperienced readmission due to a recurrence of the symptoms suffered. Depok City is one of the cities in West Java witha relatively high prevalence of heart failure, namely 4.65%, and in 2020 it ranks in the top 10 with a total of 8,543 cases(6.08%). Therefore, it is important to know whether or not there is a relationship between medication adherence and alow salt diet on the incidence of readmission in heart failure patients. This study used a cross sectional research designwith a retrospective approach. The samples taken in this study were 92 respondents with the inclusion criteria of heartfailure patients who experienced readmission within a period of 1 year at the Depok City Hospital. The samplingtechnique used in this study was a consecutive sampling technique. Collecting data using respondent data questionnaire,MMAS-8 questionnaire, and DSR-SCB questionnaire. The results showed that there was a relationship betweenadherence to medication and a low-salt diet on the incidence of readmission in heart failure patients with p value = 0.000in the first, second, and third years